1992
DOI: 10.1007/bf00016108
|View full text |Cite
|
Sign up to set email alerts
|

Lake restoration with and without dredging of phosphorus-enriched upper sediment layers

Abstract: Human activity has been the cause of continuing decline of water quality in most Dutch lakes. Development of lake restoration programmes must take into account the lake functions. Major reduction of the nutrient and pollutant loading is the primary step in lake restoration. Still, the recovery of eutrophic lakes is retarded frequently because of internal phosphorus loading by the lakes' sediments. Sediment dredging, as an additional tool for water quality management to accelerate accomplishing the desired wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…This approach has been successful in shallow lakes (Kleeberg and Kohl, 1999;Phillips et al, 1999) und would probably help lower the concentration of available phosphate in the Greifswalder Bodden. In studies of (Van Der Does et al, 1992;Van Liere and Gulati, 1992) sediment dredging lead to a marked reduction in phosphate concentration in the upper sediment accompanied by a reduced phosphorus release into the water column and a decline in phytoplankton concentration. However, lake restoration programs showed that sediment removal alone could not provide long-term changes without additional restoration measures (Ryding, 1982;Boers et al, 1992;Kleeberg and Kohl, 1999;Phillips et al, 1999), and they are an expensive restoration tool.…”
Section: Discussion the Greifswalder Boddenmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been successful in shallow lakes (Kleeberg and Kohl, 1999;Phillips et al, 1999) und would probably help lower the concentration of available phosphate in the Greifswalder Bodden. In studies of (Van Der Does et al, 1992;Van Liere and Gulati, 1992) sediment dredging lead to a marked reduction in phosphate concentration in the upper sediment accompanied by a reduced phosphorus release into the water column and a decline in phytoplankton concentration. However, lake restoration programs showed that sediment removal alone could not provide long-term changes without additional restoration measures (Ryding, 1982;Boers et al, 1992;Kleeberg and Kohl, 1999;Phillips et al, 1999), and they are an expensive restoration tool.…”
Section: Discussion the Greifswalder Boddenmentioning
confidence: 99%
“…In studies of (Van Der Does et al, 1992;Van Liere and Gulati, 1992) sediment dredging lead to a marked reduction in phosphate concentration in the upper sediment accompanied by a reduced phosphorus release into the water column and a decline in phytoplankton concentration. However, lake restoration programs showed that sediment removal alone could not provide long-term changes without additional restoration measures (Ryding, 1982;Boers et al, 1992;Kleeberg and Kohl, 1999;Phillips et al, 1999), and they are an expensive restoration tool. Treatment with aluminium-sulfate to bind phosphorus from the sediment (nutrient inactivating) has been successful in reducing the concentration of available phosphorus and improving trophic state (Cooke et al, 1986).…”
Section: Discussion the Greifswalder Boddenmentioning
confidence: 99%
“…With significant downward seepage in the lake, the chemical would also move out of the system in weeks or months when the aerobic layer is mixed with the anaerobic part by wind. In a whole lake experiment in a comparable lake, the addition of iron(III)-chloride also failed to improve water quality (Boers et al, 1992).…”
Section: Chemomanipulationmentioning
confidence: 99%
“…Since 1986 when the waste water treatment plant in the Horstermeer polder became operational, the phosphorus dynamics (sedimentation and release) at the sediment is the most important item in the lakes' phosphorus balance. Therefore, dredging of the lakes' nutrientloaded bottom sediment will be the most effective measures to reduce eutrophication ( Van der Does et al, 1992). A pilot-dredging project in this regard is to commence shortly.…”
Section: Alternativementioning
confidence: 99%